Kesalingmengertian Lek Bidayuh Pegunungan Kalimantan Barat - Fandis Nggarang (Badan Pengembangan dan Pembinaan Bahasa, 2023)
This study aims to inform intelligibility among the lects of ten Mountain Bidayuh sub-tribes, namely Tengon, Sapatoi, Butok, Liboy, Kowotn, Tamong, Tawang, Suti Bamayo, Badeneh, and Tadietn. The data was collected through participatory dialect mapping (DM), a procedure developed by Hasselbring (2010, 2012) and then modified by Anderbeck (2018). The data was then analyzed using the descriptive qualitative method. The result of dialect mapping shows us that the lects which can be paired due to having mutual intelligibility are Butok-Liboy, Liboy-Kowotn, Kowotn-Tamong, Tamong-Tawang, Tawang-Sapatoi, Sapatoi-Tengon, and Suti Bamayo-Badeneh. It is estimated that, for language conservation, speakers of both parts can share the translation material in their own lect. The results of the analysis also show that except for Tamong-Tawang and Suti Bamayo-Badeneh, intelligibility in Mountain Bidayuh tends to be formed from exposure (acquired intelligibility), especially among adult speakers. This is supported by the geographical reality in the Mountain Bidayuh, where two lects with mutual intelligibility are spoken in adjacent areas, which allows for close contact and understanding between speakers of each lect. Among the relationships of mutual intelligibility of these lects, Tamong-Tawang and Suti Bamayo-Badeneh are strongly suspected of having inherent intelligibility, because the relationships of the pair is high, marked by a good level of mutual understanding among child speakers, so the two pairs of lect can probably group themselves to form one common language. AbstrakPenelitian ini bertujuan mendeskripsikan kesalingmengertian sepuluh lek sub suku Bidayuh pegunungan, yaitu Tengon, Sapatoi, Butok, Liboy, Kowotn, Tamong, Tawang, Suti Bamayo, Badeneh, dan Tadietn di Kalimantan Barat. Data dikumpulkan melalui prosedur pemetaan dialek, sebuah prosedur yang dikembangkan oleh Hasselbring (2010, 2012) dan dimodifikasi oleh Anderbeck (2018). Data yang dikumpulkan kemudian dianalisis secara kualitatif deskriptif. Hasil proses pemetaan dialek menunjukkan bahwa lek yang memiliki kesalingmengertian adalah Butok-Liboy, Liboy-Kowotn, Kowotn-Tamong, Tamong-Tawang, Tawang-Sapatoi, Sapatoi-Tengon, dan Suti Bamayo-Badeneh. Dalam konteks konservasi bahasa, diperkirakan penutur lek yang berpasangan ini dapat berbagi materi terjemahan dalam lek mereka masing-masing. Hasil analisis juga menunjukkan bahwa, kecuali untuk Tamong-Tawang dan Suti Bamayo-Badeneh, kesalingmengertian antara lek-lek Bidayuh pegunungan lainnya cenderung dibentuk dari eksposur (acquired intelligibility), khususnya di kalangan penutur dewasa. Hal ini didukung oleh kenyataan geografis di wilayah Bidayuh pegunungan, di mana lek-lek yang memiliki kesalingmengertian dituturkan di wilayah yang berdekatan, yang memungkinkan terjalinnya kontak yang erat dan kesepahaman di antara penutur masing-masing lek. Di antara relasi kesalingmengertian lek-lek tersebut, Tamong-Tawang dan Suti Bamayo-Badeneh diduga kuat memiliki kesalingmengertian yang inheren (inherent intelligibility), karena kesalingmengertian pasangan lek tersebut begitu tinggi, ditandai oleh adanya level pemahaman yang baik di antara penutur anak-anak. Kedua pasangan lek tersebut kemungkinan dapat mengelompok sendiri dalam satu bahasa yang sama.